A systematic review of process evaluations for psychosocial interventions designed to improve the wellbeing and quality of life of community‐dwelling people with dementia and their carers. (31st October 2022) - Wyman, Danielle Laura; Butler, Laurie; Bright, Peter; Morgan‐Trimmer, Sarah; Budgett, Jessica; Cooper, Claudia
Abstract: Background: Psychosocial interventions improve the wellbeing and quality of life of People Living with Dementia (PLWD) and their family carers; but due to their complexity it can be challenging to identify mechanisms of action. We reviewed process evaluations that have sought to elucidate how these interventions work, to inform their implementation. Method: We systematically reviewed process evaluations of studies evaluating psychosocial interventions for PLWD in their own home and/or their family carers. We rated study quality using the Mixed Methods Appraisal Tool. We described, with reference to Medical Research Council (2015) process evaluation guidance, how implementation, mechanisms of impact and contextual factors were investigated; and describe commonalities in the mechanisms of action identified across studies. Results: Twenty four included studies evaluated the processes of 22 interventions. These studies collectively applied five frameworks; almost all frameworks' advised evaluations were theory‐based and used mixed‐methods analyses, but only 5/24 evaluation designs were informed by the intervention theory and 8/24 used mixed methods. 8/24 evaluations considered contextual factors in their design, though 20/24 cited contextual factors in findings. Interventions were more successful where PLWD were motivated and aware of potential benefits, and when carers could support engagement and were themselves supported by the intervention. How the intervention aligned with participants' current needs and stage of dementia were key influencing factors. Conclusion: Knowing how interventions can influence change for community‐dwelling people with dementia and their family carer's will improve translation of trial findings into practice. Robust, theory‐driven process evaluations can enable this. Key points: Interventions for people living with dementia (PLWD) at home and their family carers were more successful where the participants were motivated and aware of potential benefits. How the intervention aligned with participant's current needs and stage of dementia were key influencing contextual factors. Key influencing mechanisms of impact were provision of support for the family carer, whether through the facilitator or through peers. Influencing implementation factors related to the quality of content and flexibility of delivery of intervention components.